"Where shall I place my imaginary coterie?": Sociality and Public Discourse in Leigh Hunt’s London Journal - Lendrum, Chris (Romanticism and Victorianism on the Net, 2011)
In 1834, Leigh Hunt launched the Leigh Hunt's London Magazine with the express purpose of "bringing into public intercourse the same candour and simplicity that are practised between friends in private." While this goal could be considered to be entirely apolitical, this essay suggests that Hunt's desire to establish a close, intimate relationship with his readers is actually an attempt to resist what he felt was the degraded and impersonal nature of periodical literature. By creating a public space in his publication—a coffee-house in print, if you will—Hunt hoped to revitalize the periodical literature that he loved and, by extension, reinvigorate the public discourse that he felt had become stale and unproductive.